INOVASI TERAPI AKTIVITAS KELOMPOK PEMBUATAN LILIN AROMATERAPI SEBAGAI PENDEKATAN MODEL PRAKTIK KEPERAWATAN PROFESIONAL PADA PASIEN GANGGUAN JIWA - Arnika Dwi Asti; Darsino Darsino; Titi Pudji Rahayu; Umi Sangadah; Farhana Zahidah; Ayusta Rizka Alifa Septiono; Maylani Sofiana (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Patients with mental disorders often experience limitations in social functioning, daily activities, and interaction. Group Activity Therapy is an effective psychiatric nursing intervention to improve patients' social, cognitive, and emotional abilities. Group Activity Therapy is an integral part of the Professional Nursing Practice Model (MPKP) program in psychiatric wards. However, the implementation of Group Activity Therapy in wards is often suboptimal due to the limited variety of engaging and productive activities for patients. This community service activity aims to optimize the implementation of group activity therapy through aromatherapy candle making training for patients in the psychiatric ward of PKU Muhammadiyah Hospital, Gombong. The activity was conducted using a hierarchical approach of education, demonstration, training, and hands-on practice involving patients and healthcare workers. The activity was implemented through preparation, training, and evaluation. The activity results showed that both nurses and patients were able to participate effectively in the activities, demonstrated increased participation in group activities, and were able to independently make aromatherapy candles with nurse guidance. In addition to improving patient skills, this activity also provided a relaxing effect and increased social interaction among patients. This program can be an innovative alternative for implementing group activity therapy in psychiatric wards. Therefore, simple skills training activities such as aromatherapy candle making can be integrated as part of the Professional Nursing Practice Model in hospitals.